The Role of Gut Microbiota in the Pathogenesis and Treatment of Obesity: A Contemporary Review - Łysynkiewicz, Katarzyna; Grzyb, Izabela; Szewczyk, Jan; Wątek, Zuzanna (Quality in Sport, 2026)
Background. Obesity is a chronic disease and a global health problem contributing to increased mortality. The gut microbiota supports energy homeostasis and modulates inflammation and appetite, and may influence obesity development. Aim. To summarize evidence on the gut microbiota in obesity pathogenesis and microbiome-modulating treatments (diet, physical activity, pre-/pro-/synbiotics, postbiotics, selected pharmacotherapies). Materials and methods. Major biomedical databases were searched for experimental and clinical studies on microbiota composition/function in obesity, dysbiosis-related mechanisms, and effects of interventions on microbiota and metabolic outcomes. Results. Obesity is associated with heterogeneous but recurring alterations in microbial diversity, composition and function, including SCFA- and bile acid–related pathways and markers of impaired intestinal barrier function. Mediterranean/plant-based patterns, higher fiber intake and selected biotics most consistently improve these profiles; physical activity and some drugs show smaller, variable effects. Conclusions. Dysbiosis may contribute to obesity via metabolic and inflammatory mechanisms, but findings are context-dependent, limiting the value of simple markers. Translation to practice requires standardized methods, robust biomarkers and personalized interventions integrated with sustained healthy diet and physical activity.